Pasyente/Peryodista an exploratory study on first-person journalism in the Philippines during the Covid-19 pandemic - Comuyog, Jomira Denise R.
This study uncovered motivations behind the production of first-person journalism in the Philippines during the COVID-19 pandemic and its ethical implications to journalistic objectivity. It applied Framing Theory, Bourdieu's Theory of Practice and Ward's Rhetorical Theory of Value Change to examine how crises evolve newsroom practices and values. Ten case study texts underwent textual analysis to interpret messaging, structure and adherence to established journalistic standards stipulated in the Society of Professional Journalists' Accuracy, Fairness and Privacy checklists. In-depth semi-structured interviews were also conducted with 13 Filipino authors and newsroom representatives.